1969
DOI: 10.1007/bf02545624
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of alk‐2,4‐dienals in autoxidized lard

Abstract: Evidence suggested that the low proportions of C10 alk‐2,4‐dienal found in mildly autoxidized linoleate or lard was basically due to a selective scission mechanism of the 13 and 9 conjugated linoleate hydroperoxide isomers. Spontaneous scission tended to be at the carbon linkage between a double bond and the hydroperoxide group. Thus the 13 hydroperoxide isomer produced the typically predominant amounts of hexanal. The 9 hydroperoxide isomer formed little C10 dienal and scission between the 9 and 10 carbons po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
4
27
1
Order By: Relevance
“…Thus, the variation in the proportions of cleavage products observed in previous studies (6,20,21) is due, at least in part, to the varying degrees of carbon-oxygen bond scission that accompanied the carbon-carbon and oxygen-oxygen bond scissions. 53 the conditions of the decomposition of the hydroperoxides.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, the variation in the proportions of cleavage products observed in previous studies (6,20,21) is due, at least in part, to the varying degrees of carbon-oxygen bond scission that accompanied the carbon-carbon and oxygen-oxygen bond scissions. 53 the conditions of the decomposition of the hydroperoxides.…”
Section: Discussionmentioning
confidence: 82%
“…It has also been suggested (3,4,6) that reaction of a hydroxyl radical with an alkyl, a vinyl, or a 1,3 butadienyl radical gives rise to an alcohol, an alkanal, or a 2-alkenal, respectively, the aldehydes being formed via their enolic forms. While the manner of oxidation of unsaturated fatty acids by enzymic oxidation and autoxidation to form either single isomers or mixtures of isomers of hydroperoxides is well established, the pathway by which they decompose to yield cleavage products is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that isomerisation of the -OOH group takes place during the homolytic cleavage of linoleate hydroperoxides. Some workers (Swoboda and Lea, 1965;Kimoto and Gaddis, 1969) showed that oxidation of fats containing linoleate favours the formation of hexanal under mild conditions and 2,4-decadienal at high temperatures. On the basis of gas chromatography and infrared studies, the amounts of trans-cis and trans-trans isomers of 2,4-decadienal were reported to be 28 and 72%, respectively (Hoffmann, 1961).…”
Section: Aldehydesmentioning
confidence: 99%
“…In general, this observation is in accordance with previously reported results and recommendations (7,20,21). It has been reported that during the thermal oxidation of olive oil samples, hexanal could be generated by the thermal decomposition of linoleate 13-OOH, especially at lower temperatures (22,23). Figure 3 shows the activation energies for olive oils packaged in glass, PET, and PVC materials stored isothermally and initially at 1, 2, or 3 mon in dark conditions before exposure to light (see the description of Cases 2A-C).…”
Section: Resultsmentioning
confidence: 97%